PERANAN BIMBINGAN KONSELING BAGI GURU SEKOLAH DASAR SE-KECAMATAN KUANTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI - khairiyah Khadijah Khairiyah; Siska Mardes (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2022)
This service activity aims to enable participants to organize a Counseling Guidance program for students. This Counseling Guidance can help solve or prevent problems for students at school and in the family. The methods for implementing community service activities are lectures, demonstrations, and simple exercises in implementing guidance programs for students in elementary schools. The target of training activities in implementing this counseling guidance program is elementary school education teachers in Kuantan Hilir Seberang District, Kuantan Singingi Regency. Outcomes of Service Activities: (a) elementary school education teachers understand the basic concepts of counseling guidance, (b) basic concepts of counseling guidance in elementary schools, (c) Simple practice of implementing counseling guidance programs (types of BK services) tailored to student needs (c) primary school education teachers can implement types of counseling and guidance services that can be applied in primary school education, (f) discussions and questions and answers to discuss and explain things that participants as feedback for the trainer do not understand. Then, after the activity implementation, a new understanding was obtained for elementary school teachers that they could use BK services to solve student problems according to student needs, whereas homeroom teachers at the elementary school level.